2004
DOI: 10.1021/om0499308
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of N-Heterocycle-B(C6F5)3 Complexes. 3. Generation of N-Methylpyrrol-2-yl and N-Methylindol-2-yl Borate Zwitterions with Acidic sp3 Carbons

Abstract: The stoichiometric reactions of N-methylpyrrole and N-methylindole with B(C6F5)3 produce the zwitterionic species 2-[tris(pentafluorophenyl)borane]-5H-1-methylpyrrole (3) and 2-[tris(pentafluorophenyl)borane]-3H-1-methylindole (4), in which a C(α)−B bond and an acidic sp3 methylene carbon are formed in the heterocyclic part of the molecule. Both derivatives present a restricted rotation around the C(α)−B and/or B−C6F5 bonds, and their rotational barriers (13.8 and 14.8 kcal mol-1 for 3 and 4, respectively) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 7 publications
(10 reference statements)
3
24
1
1
Order By: Relevance
“…The 13 C NMR signal which correlates with these protons (d 76.4) also did not couple to phosphorus. These observations are consistent with the presence of acidic sp 3 protons in 5-membered N-heterocyclic compounds [18,19]. The 1 H NMR signals for the diastereotopic CH 2 P group were found as two multiplets centred at d 2.51 and 2.74; the corresponding 13 C signal appears as a doublet (J C-P = 26.6 Hz) and its coupling pattern is, as expected, altered in the 1 H{ 31 P} NMR spectrum (these 1 H NMR signals do not in fact become simple doublets of doublets as a small coupling exists between this ABX system and the AB methylene system situated on the 3-position of the pyrrole ring, as shown by 2D COSY NMR).…”
Section: H/ 1 H Correlation Experimentssupporting
confidence: 87%
See 2 more Smart Citations
“…The 13 C NMR signal which correlates with these protons (d 76.4) also did not couple to phosphorus. These observations are consistent with the presence of acidic sp 3 protons in 5-membered N-heterocyclic compounds [18,19]. The 1 H NMR signals for the diastereotopic CH 2 P group were found as two multiplets centred at d 2.51 and 2.74; the corresponding 13 C signal appears as a doublet (J C-P = 26.6 Hz) and its coupling pattern is, as expected, altered in the 1 H{ 31 P} NMR spectrum (these 1 H NMR signals do not in fact become simple doublets of doublets as a small coupling exists between this ABX system and the AB methylene system situated on the 3-position of the pyrrole ring, as shown by 2D COSY NMR).…”
Section: H/ 1 H Correlation Experimentssupporting
confidence: 87%
“…However, with B(C 6 F 5 ) 3 they give the catalytically active zwitterionic products 5a (R = Ph) and 5c (R = Cy), respectively. Some time ago Erker et al reported the abstraction of a pyrrolate ligand from Cp 2 ZrMe(NC 4 H 4 ) by B(C 6 F 5 ) 3 to give the [(1-pyrrolyl)B(C 6 F 5 ) 3 ] À anion [16] and synthesized 5H-pyrrole-B(C 6 F 5 ) 3 complex by acidification of (Et 2 O) 2 Li[(1-pyrrolyl)B(C 6 F 5 ) 3 ] [17], while Resconi and co-workers undertook a detailed study of the reaction of B(C 6 F 5 ) 3 with pyrroles, indoles, imidazoles and pyrazoles [18][19][20]. In all these cases, with the exception of N-alkyl pyrroles, the boron adds to the nitrogen atom.…”
Section: H/ 1 H Correlation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Precedence for this hypothesis is provided by the reaction of B(C6F5)3 with N-Me-indole which over 10 days affords the C2-borylated arenium species (Figure 1 middle), 9 indicating that migration of boron from C3 to C2 can occur in indoles in the absence of an effective exogenous Brønsted base.…”
mentioning
confidence: 99%
“…[28] Borylation of N-methylindole afforded exclusively the 3-substituted regioisomer, in sharp contrast to the previously reported reaction with B(C 6 F 5 ) 3 , which produces the 2-borylated N-methylindole. [29] Pyrrole 15c gave a mixture of mono-borylated regioisomers along with some of the diborylated 16c using one equivalent of 8a (ca. 80% conversion of 15c ), but two equivalents of the borylating agent cleanly produced the diborylated pyrrole 16c .…”
mentioning
confidence: 99%